MI5 and the Cold War in South-East Asia: examining the performance of Security Intelligence Far East (SIFE), 1946–1963. Issue 6 (19th September 2017) - Shaw, Alexander Nicholas
Abstract: From 1946–1963, MI5 operated a South-East Asian regional headquarters in Singapore: Security Intelligence Far East (SIFE). This article responds to growing interest in theatre-level intelligence organisation and the importance of intelligence to Britain's Cold War and decolonisation by examining the performance of SIFE. On the organisational level, SIFE was strongest when it remained wedded to its charter functions and closely adhered to the priorities of its principal consumer: the Commissioner-General for South-East Asia. Its assessments were influential in shaping decision-makers' understandings of key regional developments, although this did not always translate into public policy. Lastly, SIFE enjoyed success in developing lasting liaison relationships to cement British influence, but failed to utilise these to improve its intake of raw intelligence.